Effects of Cold and Heat Stress on Egg Quality Traits of a Newly Developed Native Hybrid Layer - İsmail Durmuş; Serdar Kamanlı (Turkish Journal of Agriculture: Food Science and Technology)
ATAK-S is a newly developed native hybrid layer. Although the laying performance of this hybrid has been studied and determined, the performance response of the hybrid to different environmental temperature conditions is not known. This study was therefore undertaken to determine the effect of cold and heat stress on egg quality traits. Hens were divided into three different groups; control (20°C), low (12°C) and high (32°C). A total of 360 hens, with 120 in each of the groups, were used in the study. Hens were held in three tier battery cages in an environmentally controlled poultry house. The study lasted for 3 weeks. No differences were found among different groups in terms of shape index, albumen height and Haugh unit of the egg quality traits. It was found that the differences among the heat groups in terms of egg shell breaking strength, egg weight, shell thickness and yolk colour were significant and the value of these traits decreased under the heat stress conditions, whereas they were not affected from the cold stress.